Ovarian Papillary Cystadenoma with Pyometra Cystic Endometrial Hyperplasia Complex in a Bitch - Gopikrishnan, Duraisamy; Selvaraju, Mani; Periyannan, Mani; Ravikumar, Kaliannan; Arulmozhi, Ayyasamy; Varudharajan, Venkatraman (Indian Journal of Veterinary Sciences and Biotechnology, 2021)
Canine pyometra is a diestrual disorder and a more common condition in older bitches (>7 years) that is often life-threatening. Cystic endometrial hyperplasia (CEH) is a subclinical condition characterized by the proliferation of endometrial glands resulting in the formation of fluid-filled cysts with luminal uterine contents (Schlafer and Gifford, 2008), and this allows bacterial proliferation in the uterus at diestrus under the influence of progesterone which results in the formation of pyometra (Verstegen et al., 2008). The concurrent occurrence of Pyometra-CEH complex with an ovarian tumor is rare and often taken as a severe threat to act immediately. In the present case, the concurrent occurrence of ovarian papillary cystadenoma with pyometra-CEH in a bitch is reported and discussed.